Perkembangan Seni Beladiri Tarung Derajat di Indonesia Tahun 1972-2017 - Ardi Wira Azhari; Fajriudin Fajriudin; Yosep Mardiana (UIN Sunan Gunung Djati Bandung, 2018)
Tarung Derajat is a type of native Indonesian martial arts originated from Bandung on July 18, 1972 by one of the sons of the nation namely Achmad Drajat. At first Tarung Derajat was established only to defend themselves from attacks by people, but over time Tarung Derajat became a martial arts achievement sport. This study aims to find out how the history of the establishment of Tarung Derajat and find out how the development of Tarung Derajat Martial Arts in Indonesia in 1972-2017. This research method is carried out through four stages, namely heuristics, criticism, interpretation, and historiography. From the results of this study it can be concluded that: first, the birth of Tarung Derajat martial arts is motivated by Achmad Drajat's who found 5 (five) forces, namely: strength - speed - accuracy - courage - tenacity that aims to increase human dignity. Secondly, what was originally only a hard work, then in 1997 Tarung Derajat became a member of the Central KONI and was able to take part in the championships held by KONI. Third, the development of Tarung Drajat is very rapid, this original Indonesian martial arts has now penetrated other countries such as Malaysia so that there is a desire for Tarung Derajat to compete in the Sea Game.